The usage of digital marketing tools among Vietnamese B2B start-ups in building customer relationships - Trung, Nguyen Tran (Tạp chí Nghiên cứu Tài chính - Marketing, 2024)
Digital marketing has been being widely used around the world and changing at a rapid rate. For small businesses, especially start-ups, digital marketing is bringing new opportunities to meet the goals that were previously impossible to achieve. However, many micro-enterprises are not utilising digital marketing to its full potential. The main aim of this study is to investigate the e-marketing model of Vietnamese B2B start-ups as well as the usage and changes of digital marketing tools. In-depth interviews with three main themes were conducted with newly founded and mature Vietnamese B2B start-ups in different sectors. Attracting, engaging, retaining, learning, and relating to customers are critical elements to building customer relationships. In terms of importance, the rankings of these five elements vary depending on each company’s current goals and objectives.. While newly founded start-ups concentrate on attracting customers, mature ones focus more on engaging, retaining, and learning customers. Moreover, a significant change in theoretically recognized and utilized tools through 2017-2023 is documented. Throughout the six years, many out-of-date and inefficient tools have been eliminated. Other newer and more valuable tools have been becoming widely used, especially LinkedIn which has become one of the primary social media platforms. It is also emphasized that although new digital marketing tools have been adopted among Vietnamese B2B start-ups, They have not been exploited to their full potential. The reasons behind the changes in the usage of digital marketing tools lie in three main categories, which are firm-specific and owner-manager factors, resource-related factors, and environmental factors.